Working with International Students in the U.S. and Beyond: A Summary of Survey Research by NCDA International Student Services Committee - Balin, Elif; Anderson, Nicole M.; Chudasama, Satomi Y.; Kanagasingam, Sutha K.; Zhang, Lily (Journal of International Students, 2016)
The career development process is one of the most important aspects of the international student experience. Providing comprehensive and culturally competent services requires institutional efforts that utilize best practices developmentally throughout the college experience and beyond. This article is based on the work of the International Student Services Committee of the National Career Development Association, especially the surveys conducted with international students, career development professional and employers. The authors focus on three major themes from the surveys: knowledge about work authorization options, impact of cultural differences on job search, and specialized career services for international students. Discussing these major themes, the authors report on best practices and future implications for supporting international student career development in the U.S. and beyond.